Rapid biodegradation of chlorpyrifos by plant growth-promoting psychrophilic Shewanella sp. BT05: An eco-friendly approach to clean up pesticide-contaminated environment. (May 2020) - Govarthanan, M.; Ameen, Fuad; Kamala-Kannan, S.; Selvankumar, T.; Almansob, A.; Alwakeel, S.S.; Kim, Woong
Abstract: The present study explores the rapid chlopyrifos (CPs) biodegradation potential of plant growth promoting (PGP) psychrophilic bacteria isolated from brackish water by enrichment culture technique. Based on biochemical tests and 16 S rDNA sequencing the isolate was identified as Shewanella sp. The isolate Shewanella BT05 showed significant growth rate in various concentrations of (10–50 mg/L) CPs. The isolate produced plant growth promoting factors, IAA (20.8 ± 1.2 and 15.4 ± 1.0 μg/mL) and siderophores (60.67 ± 1.2 and 57.5 ± 0.9%) in the absence and presence of CPs. Further, the isolate BT05 solublized phosphate (16.5 ± 1.0 and 12.0 ± 1.0 mm in size respectively), and produce hydrogen cyanide (excellent and moderate) in the presence and absence of CPs. The isolate BT05 degraded 94.3, 91.8, 87.9, 82.6, and 80.5% of CPs at 10, 20, 30, 40, and 50 mg/L, respectively, within 24 h. Further, the media conditions were optimized for enhanced CPs removal and observed 93% removal in the presence of 3.5% glucose in pH 7.0 at 32.5 °C. Fourier-transform infrared spectroscopy and high-performance liquid chromatography results indicated the role for Shewanella BT05 in the biomineralization of CPs. The results suggested the isolate BT05 could be used for CPs removal as well as PGP activity in contaminated soil. Highlights: The isolate Shewanella sp. BT05 showed rapid degradation of CPs (94.3%) within 24 h. Optimization studies showed that 13% increased CPs removal (93%) in the presence of 3.5% glucose, pH 7.0 and 32.5 °C. 3, 3, 6-trichloro-2-pyridinol (TCP), metabolic product was observed in the CPs treated with Shewanella sp. BT05.